CREATING THE TAMBUN BUNGAI BATIK MOTIF AS AN ALTERNATIVE BRAND IDENTITY FOR CENTRAL KALIMANTAN - Nawung Asmoro Girindraswari; Bayu Prihantoro (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Developing batik motifs with the character of a region is one potential way to create new, contemporary motifs by tapping into the region's potential. Tambun and Bungai are taken from the names of two well-known and renowned heroes in the folk stories of the Dayak people in Central Kalimantan Province, Kalimantan Tengah. They are seen as having prominent cultural aspects that can represent Central Kalimantan and be transformed into a form of visual branding. There are many potentials in Central Kalimantan that can be developed into iconic motifs, such as from local customs, natural resources, and ecotourism. Therefore, there is a need to create a Tambun Bungai motif that is in line with the local wisdom and characteristics in an effort to promote Central Kalimantan through batik media. This article is part of an effort to establish the brand identity of Central Kalimantan through in-depth research on the local cultural identity, with the output being the creation of a decorative pattern called the Tambun Bungai batik motif.